2001
DOI: 10.1002/1521-3765(20010716)7:14<3062::aid-chem3062>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (E)-α,β-Unsaturated Amides with High Selectivity by Using Samarium Diiodide

Abstract: Stereoselective beta-elimination of 2-chloro-3-hydroxyamides 1 is achieved by using samarium diiodide to yield alpha,beta-unsaturated amides 2, in which the C=C bond is di- tri-, or tetrasubstituted. The starting compounds 1 are easily prepared by reaction of the corresponding lithium enolates of alpha-chloroamides with aldehydes or ketones at - 78 degrees C. The influence of the reaction conditions and the structure of the starting compounds on the stereoselectivity of the beta-elimination reaction is also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Our first attempt involved the stereoselective synthesis of tetrasubstituted α , β ‐unsaturated amides 2a using the Concéllon et al . procedure . This method is based on reductive elimination of α , β ‐epoxyamides or 2‐chloro‐3‐hydroxyamides using SmI 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our first attempt involved the stereoselective synthesis of tetrasubstituted α , β ‐unsaturated amides 2a using the Concéllon et al . procedure . This method is based on reductive elimination of α , β ‐epoxyamides or 2‐chloro‐3‐hydroxyamides using SmI 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Melting points are uncorrected. 1 H NMR spectra were recorded on a Bruker 400 MHz instrument as CDCl 3 solutions using TMS as internal standard. Chemical shifts (d) are reported in ppm and coupling constants J are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Concellón et al 1 reported a stereoselective b-elimination of 2-chloro-3-hydroxyamides using samarium diiodide (SmI 2) to synthesize a,b-unsaturated amides. Herein we wish to describe an alternative way employing SmI 2 to prepare a,b-unsaturated amides from nitro compounds and a,b-unsaturated esters.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Imamoto et al described the cyclopropanation of lithium enolates derived from ketones by using SmI 2 / CH 2 I 2 . [13] Recently, we described the SmI 2 -promoted highly diastereoselective synthesis of vinyl halides, [14] a,b-unsaturated esters [15] and amides, [16] deuterated b,g-unsaturated esters, [17] and vinylsilanes. [13] Recently, we described the SmI 2 -promoted highly diastereoselective synthesis of vinyl halides, [14] a,b-unsaturated esters [15] and amides, [16] deuterated b,g-unsaturated esters, [17] and vinylsilanes.…”
mentioning
confidence: 85%